METHODOLOGY OF ANALYZING PRE-INJURY, INJURY SITUATIONS AND INDUSTRIAL INJURIES IN AGRO-ENGINEERING - Kostenko, O. M.; Opara, N. M.; Drozhchana, O. U. (Scientific Progress & Innovations, 2020)
In Ukraine, according to the data of the International Labor Organization, industrial injuries are nearly the most numerous among European countries. Mortality from such injuries takes the third place after cardio- vascular and oncological diseases. Death injuries are most frequent in agro-industrial complex: in 2019, 80 employees died, which is 19 % more than in 2018. That is why the problem of decreasing the number of industrial injuries is topical. To solve it studies are conducted using various methods and techniques. The analysis of researches of foreign and Ukrainian scholars has shown that the existing methods do not cover the whole picture of the problem. They consider environmental circumstances, but do not take into account the circumstances, which are directly or indirectly connected with organizational and technical work to prevent injuries, with the system of industrial safety management, with sanitary and hygienic, regulatory-legal, engineering and technical, medical and biological, psychic-physiological, ergonomic and other provisions. The technology of analyzing industrial injuries was proposed in the paper, covering circumstances, sources, and reasons resulting in traumatism, especially those cases, which in particular situation led to injuries. In other words, it has been suggested to analyze pre-injury situations, which are production backgrounds of injuries’ occurring or not occurring. This analysis technology enables to plan measures, which make it impossible for injury dangerous situations and injuries to happen. The technology of generating and analyzing pre-injury situations has been developed in the paper. Considering such technology, it is clear that technological processes and production are the whole. To develop preventive measures, the technology of traumatism analysis and ways to prevent it has been proposed. The technology consists of 5 blocks: traumatism indices, dynamics during the years of analysis, analysis of prognostication results, substantiation of preventive measures, and implementation of them. The suggested methodology is an important component of the strategy and tactics of dynamic decreasing and eliminating industrial injuries. It is recommended to use the given methodology while analyzing industrial traumatism and developing preventive measures in all fields of economic activity.